2019
DOI: 10.1109/temc.2018.2864199
|View full text |Cite
|
Sign up to set email alerts
|

Line Charge Densities and Currents of Downward Negative Leaders Estimated From VHF Images and VLF Electric Fields Observed at Close Distances

Abstract: The channel charge distribution of a lightning leader is a critical parameter for the study of lightning mechanism. However, there is little experiment-based result on it, mainly due to lacking adequate methods for getting the leader charge distribution with ordinary ground observations. In this paper, a method for retrieving the line charge density and the current of a downward leader based on ground observations of lightning images and electric field changes was proposed and examined. The method was then app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…The transferred line charge density of DPL1 ranges in 0.4 to 8.6 mC/m with the peak appearing at 1,750 m high, and that of DPL2 ranges in 0.4 to 15.2 mC/m with the peak appearing at 2,635 m high. While the transferred line charge density for the upper part of the leader channel is higher, that for the lower part of the leader channel is comparable to most of previous results (e.g., Chen, Zheng, et al, 2013 ; Proctor, 1997 ; Shen et al, 2018). The leader current of DPL1 ranges in 0.7 to 5.4 kA with a mean of 3.7 kA and that of DPL2 ranges in 0.7 to 4.6 kA with a mean of 2.3 kA. The ambient electric field for both leaders has an alternating polarity along the leader path.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The transferred line charge density of DPL1 ranges in 0.4 to 8.6 mC/m with the peak appearing at 1,750 m high, and that of DPL2 ranges in 0.4 to 15.2 mC/m with the peak appearing at 2,635 m high. While the transferred line charge density for the upper part of the leader channel is higher, that for the lower part of the leader channel is comparable to most of previous results (e.g., Chen, Zheng, et al, 2013 ; Proctor, 1997 ; Shen et al, 2018). The leader current of DPL1 ranges in 0.7 to 5.4 kA with a mean of 3.7 kA and that of DPL2 ranges in 0.7 to 4.6 kA with a mean of 2.3 kA. The ambient electric field for both leaders has an alternating polarity along the leader path.…”
Section: Discussionsupporting
confidence: 89%
“…For a lightning leader, the transferred line charge density along the leader channel is defined as λ = dQ/dl , where dQ is the charge transferred from the cloud into a channel segment of length dl . In previous studies (Chen, Zheng, et al, 2013; Shen et al, 2018), a basic assumption was that charges being added to the leader tip were transferred directly from the electric source in cloud/ground and charges along the established channel behind the leader tip kept unchanged as the leader developed, which is adopted in this study too. For the electric field measurement at TOLOG, because the observation site is several kilometers away from the cloud and the lightning channel, the electric charge source in cloud can be simplified as a point charge.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physics sign convention for the electric field was used in this paper (upward directed field is positive). It is worth noting that here we present a limited number of cases that are representative of common processes, having in mind uncertainties in input variables, including the input geometry, line charge density (e.g., Gao et al., 2020; Shen et al., 2019) and velocity of leaders (e.g., Campos et al., 2014; Proctor, 1997). An open‐source code with a graphical interface is provided as supporting information.…”
Section: Electric Field Characteristics Of the Considered Scenarios F...mentioning
confidence: 99%
“…The peak currents range from −5 to −40 kA. These values are one to two orders of magnitude larger than peak currents of downward stepped leaders inferred from magnetic or electric field observations (Shen et al., 2019; Thomson et al., 1985; Williams & Brook, 1963) and upward negative leaders in triggered lightning or from tall objects (Miki et al., 2014; Pu et al., 2017; Watanabe et al., 2019; Zhou et al., 2012). In fact, strong strokes analyzed in this study are almost always preceded by clear leader pulses as shown in Figures 1a–1j, indicating strong peak currents of stepped leaders.…”
Section: Resultsmentioning
confidence: 72%